UZBEKISTAN IN THE CONTEXT OF THE GLOBAL FINANCIAL AND ECONOMIC CRISIS - KARIMOVA, Dilshojon (CENTRAL ASIA AND THE CAUCASUS, 2009)
The most urgent tasks of the present day are to make an objective assessment of the reasons for the emergence of the global financial and economic crisis that broke out in 2008 and draw up a program of measures for overcoming its negative consequences. As world experience shows, crises inevitably give rise to political instability and an increase in crime and corruption throughout the world (for example, the 1847-1849 crisis led to revolutions in many European countries, while the Great Depression of 1929 generated Fascism). Moreover, such conditions may cause an abrupt change in the functioning of political institutions and push to the foreground aggressive forces that used to be considered secondary and marginal (anarchism, Nazism, neo-Fascism, and racism). The elections held recently in the European countries (including to the European Parliament) are clear proof of the real possibility that such threats may arise. But during the first weeks of 2008, essentially all international experts regarded the situation in the world economy as favorable. Society did not take the warnings of some analysts about the impending crisis seriously.